2018
DOI: 10.1002/jcb.27099
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA lung cancer associated transcript 1 promotes proliferation and invasion of clear cell renal cell carcinoma cells by negatively regulating miR‐495‐3p

Abstract: Recently, long noncoding RNAs have emerged as new gene regulators and prognostic markers in several cancers, including renal cell carcinoma (RCC). Here, we focused on the long noncoding RNA lung cancer associated transcript 1 (LUCAT1) based on clear cell RCC (ccRCC) the cancer genome atlas (TCGA) data. However, whether aberrant expression of LUCAT1 in ccRCC is correlated with malignancy, metastasis or prognosis has not been elucidated. In the current study, we found that the expression of LUCAT1 was upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 28 publications
1
34
1
Order By: Relevance
“…Lung cancer‐associated transcript 1 is located on chromosome 5 and was first observed in the airway epithelium of smokers and in various cancer cell lines . In addition to lung cancer, LUCAT1 has also been reported to be involved in esophageal cancer, renal cell carcinoma, and cisplatin‐resistant ovarian cancer . Like other lncRNAs, LUCAT1 participates in carcinogenesis and cancer progression by regulating gene expression through chromatin modification, transcription, and post‐transcriptional procession.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer‐associated transcript 1 is located on chromosome 5 and was first observed in the airway epithelium of smokers and in various cancer cell lines . In addition to lung cancer, LUCAT1 has also been reported to be involved in esophageal cancer, renal cell carcinoma, and cisplatin‐resistant ovarian cancer . Like other lncRNAs, LUCAT1 participates in carcinogenesis and cancer progression by regulating gene expression through chromatin modification, transcription, and post‐transcriptional procession.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-495-3p may have an oncogenic or anticancer effect in several cancers. For instance, miR-495-3p inhibits proliferation and invasion in clear cell renal cell carcinoma cells 12. miR-495-3p serves as a tumor suppressor by regulating multiple epigenetic modifiers in gastric carcinogenesis 13.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports demonstrated that LUCAT1 is often upregulated in several types of cancer cells and promotes the proliferation, invasion or migration of these cells from many cancer types including CRC [23][24][25][26][27][28][29][30][31][32][33]. LUCAT1 can act as microRNA sponge [25,[29][30][31][32], or bind proteins, such as DNMT1, to regulate their stabilities or activities [23,24,26,28]. In the present study, we identified that hypoxia-induced LUCAT1, mainly located in the nucleus of CRC cells, which is physically interacts with an RNA-binding protein PTBP1 and regulates mRNA alterative splicing pathway.…”
Section: Discussionmentioning
confidence: 99%